The gym group private equity challenge–group F company and market overview - Noack, Maria (2020)
TheoverallgoalofthisthesisistheevaluationofTheGymGroup’sfeasibilityasapotentialleveragedbuyouttarget.Inthebeginning,thefirmwasinspectedfromdifferentangles,themarketthoroughlyanalyzedandthecompany’spositioninthemarketassessed.Inthefollowing,acomprehensiveappraisalofinfluencingfactorsonitsfinancialperformancewasconductedandgrowthdriversforecastedtocomeupwiththreedifferentcasesofhowthefirmmightdevelop.Thisknowledgewasquantifiedandthecompanysubsequentlyvaluedusingacomparablecompany,aprecedenttransaction,aDCFvaluationmethodaswellasanLBOmodel.Additionally,aninvestmentthesisandfuturestrategyregardingtheoperationsofthetargetandtheresponsibilitiesofaPEfund,suchassourcingandanexitstrategy,weredeveloped.Finally,potentialreturnswerecalculatedforthedifferentscenarios.Thefirstpartisconcernedwiththeassessmentofthecompanyandthemarket.